Pemberdayaan Masyarakat melalui Pembuatan Pisang Crispy sebagai Sosiopreneur Baru Usaha Produk Lokal di Desa Ngunut, Jumantono Karanganyar: Community Empowerment through the Making of Crispy Banana as a New Sociopreneur for Local Product Business in Ngunut Village, Jumantono Karanganyar - Alvien Gusti Prasditio; Adestra Ayub Syawala; Aisyah Taqiyyah Faizah; Alifia Cerista Mardani; Ananda Rizky Widodo; Camellius Dellelis Gitom Pamungkas; Firyal Labibah Hambali; Grefta Jassika Sanni; Hafshah Azizah; Maheswari Candraningtyas; Marshanda Eka Salsabila; Mayliana Eka Kurniasari; Nur Ismail Darojat; Zuhrifa Sabilla Firdaus; Zulfah Nur Miftahul Hilmy; Ernoiz Antriyandarti (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Ngunut Village is located in West Karanganyar Regency, Central Java and 33.3 km far to the east of Surakarta City. This village is 485.57 ha large. The natural resources of Ngunut Village has a lot of diversification. Various agricultural products, especially plantations in Ngunut Village, include bananas. Community empowerment activities in Ngunut Village, it is carried out using the Focus Group Discussion method and training, with the target of PKK women in Ngunut Village which will later form a new sociopreneur that is more focused on the production of crispy bananas. The empowerment method used is a participatory approach. The results of the FGD obtained information that people's knowledge about processed banana products into banana chips is still low, knowledge in managing a business is still low, there is no clear structure of the crispy banana business group. The results of community empowerment for the development of crispy banana products include training on making banana chips, and improving packaging so that the product can be marketed outside the Karanganyar area.